Sistem Evaluasi Kinerja Guru Menggunakan Fuzzy Inference System Metode Tsukamoto (Studi Kasus: SMK Darur Roja) - Rahayu, Ayu; Haryono, Wasis (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
The teacher performance evaluation at SMK Darur Roja is often conducted conventionally and subjectively, making it less effective and accurate. This study aims to develop a web-based teacher performance evaluation system using the Fuzzy nference system (FIS) Tsukamoto method to provide more objective and transparent assessments. The system utilizes four main criteria: pedagogical, personal, professional, and social competencies, weighted at 35%, 25%, 25%, and 15%, respectively. Evaluation data is processed using the Tsukamoto method, which converts linguistic values into quantitative ones to produce measurable decisions. The system was implemented using PHP and MySQL with a waterfall development approach. Testing results indicate that the system can provide accurate and reliable evaluations, supporting decision-making in managing teacher performance. This system is expected to enhance teaching quality and overall education standards at SMK Darur Roja.